Memahami Absurditas Intermestik Indonesia - Pradana, Adi Mulia (Global and Policy Journal of International Relations, 2014)
ABSTRACTAs a country which has now become the main driving force of the economy of ASEAN, Indonesia not only has the responsibility to maintain the stability of the leadership of the economy. But also give concrete solutions and take action so that ASEAN is no longer experiencing economic crisis. As well as the views of the current state of contemporary, reducing the risk of slowing global economy as still the continued economic crisis in Europe. Each country has the right to present policy options cannot be dipkasa uniformly in the handling of the impact of the recession. The role of Indonesia in the present policy line towards the AEC, analyzed its effectiveness maintain regional economic stability associated components supporting Indonesia's domestic economy. The Problem of perception in intermestik, between the reality in the domestic and foreign expectations against Indonesia, should make Indonesia not to run against a variety of things that are actually quite trapping many parties in Indonesia in facing the economic growth rate of Indonesia itself. Do the optimization of economic growth over reducing inequality in the domestic economy, will be the key to how Indonesia can play a role in economic balance in the region.Keywords: intermestic, ASEAN Economic Community, balance, gap, economic growth.DOI:https://doi.org/10.33005/jgp.v2i01.1976